Expression of antimicrobial peptides and E‐cadherin in periapical lesions. Issue 2 (18th January 2013) - Ishihata, Kiyohide; Kume, Kenichi; Hijioka, Hiroshi; Kibe, Toshiro; Tanaka, Shoko; Komatsuzawa, Hitoshi; Harada, Hidemitsu; Nakamura, Norifumi
Abstract: Objective: Radicular cysts and apical granulomas are inflammatory diseases that develop in association with an infected root canal. It is thought that persistent inflammation may stimulate proliferation of dental epithelial cells around the root to form a cyst. However, pathogenesis and the mechanism of epithelial proliferation have not been clarified. The purpose of this study is to examine the levels of chemical and physical antimicrobial activities of periapical lesions. Methods: To explore the expression of antimicrobial peptides (AMPs) and E‐cadherin in periapical lesions, 10 tissue specimens each of apical granulomas and radicular cysts were evaluated by immunohistochemistry using anti‐AMPs [human neutrophil defensin (HNP), LL37, human beta‐defensin (HBD)‐1 and ‐2] and anti‐E‐cadherin antibody. In vitro assay to assess the expression of LL37, HBD‐1, ‐2 and E‐cadherin in the immortalized rat dental epithelial cell line (HAT‐7) stimulated with/without lipopolysaccharide (LPS) or bacterial cells were detected by immunocytochemistry, quantitative real‐time polymerase chain reaction and Western blot analysis. Cell proliferation after incubation with/without LPS or LL37 was assayed by MTT assay. Results: HNP and LL37 were observed mainly in the neutrophils of apical granulomas, while HBD‐1 and E‐cadherin showed higher expression in radicular cysts than in apical granulomas. In vitro assays showed that bacterial stimulation enhanced expression of HBD‐2, LL37, and E‐cadherin, but epithelial cell proliferation was not enhanced with LPS and LL37. Conclusions: These observations suggest that dental epithelial cells can secrete AMPs and consolidate epithelial intercellular junctions when stimulated by bacterial infection, and radicular cysts may play an important role in defense mechanisms.